Targeted Drug Delivery Using Artificial Intelligence for Nano carrier Design (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
The drug delivery system is of great importance for the efficacy of a medicine to reach the target site in the body. Nanocarriers have played an important role in enhancing drug stability, controlled release, and targeting action. Despite these improvements, the design of an ideal nanocarrier remains a complex and time-consuming task. Artificial intelligence (AI) is revolutionizing this field, making the development of nanocarriers faster, smarter and more accurate.AI techniques such as machine learning and deep learning can be used to analyze large pharmaceutical and biological data to predict the best materials, particle size, drug-loading capacity, release pattern and targeting efficiency of nanocarriers. This minimizes the need for repeated laboratory experiments, saving time and research cost. It also allows researchers to more accurately identify the best formulations to increase the likelihood of successful drug delivery.One of the most promising applications of AI-driven nanomedicine is cancer therapy, where drugs can be delivered directly to tumor cells while minimizing damage to healthy tissues. Such a targeted approach can improve the effectiveness of treatment and reduce unwanted side effects. Besides, AI allows developing customized drug delivery systems that take into account patient-specific characteristics paving the way for precision medicine.It has great potential, but there are still many challenges which remain. These include the need for high-quality datasets, reliable model validation, ethical considerations and regulatory approval. Addressing these challenges will be key to wider clinical adoption. The synergy of artificial intelligence and nanomedicine is a landmark in pharmaceutical science and is expected to transform the future of targeted drug delivery through safer, more effective, and patient-centric therapeutic approaches.
Keywords: Artificial Intelligence; Nano medicine; Targeted Drug Delivery; Machine Learning; Precision Medicine